India [sic] Woman, Trinidad, B.W.I. - (:unkn) unknown ([Printed in Germany], 2008)
Hand painted image of an East Indian woman in traditional wear.
Colour: Red, Yellow, Green and White Hues; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Women, East Indian--Trinidad and Tobago; Ethnic costume--India; Trinidad and Tobago; Nose rings--India